2021
DOI: 10.3390/plants10102016
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging Activity of Infusions of Different Medicinal Plants for Use in Obstetrics

Abstract: An X-band (9.3 GHz) electron paramagnetic resonance (EPR) spectroscopy was used to examine the free radical scavenging activity of the following infusions, which were nonirradiated and exposed to UVA: root of Asparagus racemosus and herbs of Mitchella repens, Cnicus benedictus L., Galega officinalis L., and Eupatorium cannabinum L. The plant materials for obstetrics applications were chosen for analysis. The aims of these studies were to compare the free radical scavenging ability of the tested infusions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Oxidative stress may come from either an excess of free radical generation or a breakdown of antioxidant defense systems (Torun et al, 2009). It has been reported that some herbs possess strong radical-scavenging ability (Jarco et al, 2021). In the current study, PCHM was added to the diet to effectively improve the free-radical scavenging capacity and reduce the content of MDA in liver, magnum, and uterus.…”
Section: Discussionmentioning
confidence: 83%
“…Oxidative stress may come from either an excess of free radical generation or a breakdown of antioxidant defense systems (Torun et al, 2009). It has been reported that some herbs possess strong radical-scavenging ability (Jarco et al, 2021). In the current study, PCHM was added to the diet to effectively improve the free-radical scavenging capacity and reduce the content of MDA in liver, magnum, and uterus.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, UVA radiation may increase the risk of skin cancer [111]. Jarco et al [112] declared that UVA radiation reduces the antioxidant interactions of all of the investigated infusions, particularly the infusion of the E. cannabinum L. herb, which should be protected from UVA radiation during storage. Table 2 presents the potency of the radical scavenging activity from Eupatorium species.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…A lot of natural compounds including alkaloids, phenolics, and terpenes in chrysanthemum have been identified as antioxidants [ 6 ]. For them, the predominant effects may involve the activation of Nrf2-related antioxidant pathways and scavenging of free radicals [ 7 , 8 , 9 ]. However, researchers found that the biological activities of natural extracts are much higher than those of single bioactive molecules due to the interaction between molecules at pharmacodynamic and pharmacokinetic levels, suggesting that the synergistic effect between multiple compounds cannot be overlooked [ 10 ].…”
Section: Introductionmentioning
confidence: 99%